Electrodes: A Comparative Study on Optical, Electrical, and Mechanical Properties of Conducting Polymer‐Based Electrodes (Small 41/2015). Issue 41 (November 2015) - Lee, Seungae; Hong, Jin‐Yong; Jang, Jyongsik
Abstract : A transparent, free‐standing, conducting polypyrrole film is composed of highly uniform polypyrrole nanoparticles. As shown on page 5498 by J. Jang and co‐workers, the film is composed of highly uniform and densely packed polypyrrole nanoparticles. Because of this structure, the free‐standing polypyrrole film exhibits high transparency, flexibility, electrical conductivity, and stable mechanical properties. The schematic illustration in this image represents these outstanding properties of the film.